Estimation of Global Cardiovascular Risk in Hypertensive Patients from the University of Medical Sciences of Cienfuegos - Lucía Baños Leyva; Milagros Lisset León Regal; Luis Alberto Mass Sosa; Jacqueline Zamora Galindo; José Andy Hernández Quintana; Judeny Colls Cañizares (Universidad de las Ciencias Médicas de Cienfuegos, 2023)
Background: despite the importance of calculating global cardiovascular risk in hypertensive patients and the benefits of its implementation in Primary Health Care, studies on its estimation are insufficient at the University of Medical Sciences of Cienfuegos. Objective: to determine the global cardiovascular risk in hypertensive patients at the University of Medical Sciences of Cienfuegos in the year 2021. Methods: a descriptive, cross-sectional and correlational study was carried out. The sample consisted of 105 hypertensive patients between 40-80 years of age from the University of Medical Sciences of Cienfuegos in 2021. The variables studied were: age, gender, total cholesterol, smoking, systolic blood pressure, diagnosed diabetes mellitus, and global cardiovascular risk. The absolute and relative frequency of the variables were calculated and Pearson's Chi square was applied in the association of the variables and low cardiovascular risk with a significance level of p=0.05. The results were presented in tables. Results: the female gender, the age group of 50-69 years, non-diabetics and non-smokers, with normal cholesterol and prehypertensive predominated. 93.3 % presented low overall cardiovascular risk and 6.7 % moderate to critical. Non-diabetic patients with normal systolic blood pressure presented a significant association with low cardiovascular risk. Conclusions: hypertensive patients at the University of Medical Sciences of Cienfuegos have a low overall cardiovascular risk, a correlation was shown between low cardiovascular risk and normal systolic blood pressure and a history of non-diabetes, which would determine protection against cardiovascular and cerebrovascular events in the future